2021
DOI: 10.3390/cancers13184621
|View full text |Cite
|
Sign up to set email alerts
|

Responses to SARS-CoV-2 Vaccination in Patients with Cancer (ReCOVer Study): A Prospective Cohort Study of the Hellenic Cooperative Oncology Group

Abstract: Data on the effectiveness and safety of approved SARS-CoV-2 vaccines in cancer patients are limited. This observational, prospective cohort study investigated the humoral immune response to SARS-CoV-2 vaccination in 232 cancer patients from 12 HeCOG-affiliated oncology departments compared to 100 healthcare volunteers without known active cancer. The seropositivity rate was measured 2–4 weeks after two vaccine doses, by evaluating neutralising antibodies against the SARS-CoV-2 spike protein using a commerciall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
43
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(48 citation statements)
references
References 53 publications
(62 reference statements)
2
43
1
1
Order By: Relevance
“…Another report did not specify the enrolled population. In 17 out of 23 studies, current smokers showed significant lower antibody titre, and in a few reports, highlighted a more rapid lowering of the vaccine-elicited IgG compared with nonsmokers [19,20,[26][27][28][29][30]32,34,[36][37][38][39][40][41]43,44]. In particular, accelerated antibody decline was reported in the prospective assessments by Ferrara et al [20], Zhang et al [27], and Malavazos et al [30].…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…Another report did not specify the enrolled population. In 17 out of 23 studies, current smokers showed significant lower antibody titre, and in a few reports, highlighted a more rapid lowering of the vaccine-elicited IgG compared with nonsmokers [19,20,[26][27][28][29][30]32,34,[36][37][38][39][40][41]43,44]. In particular, accelerated antibody decline was reported in the prospective assessments by Ferrara et al [20], Zhang et al [27], and Malavazos et al [30].…”
Section: Resultsmentioning
confidence: 92%
“…The vast majority of the current body of evidence suggests that smoking has a negative impact on the humoral response to COVID-19 vaccines, with both potential lower response and more rapid lowering of the vaccine-elicited IgG titres. However, the literature available so far does not allow us to firmly ascertain whether the effect is related to duration of smoking or number of cigarettes smoked per day [20,31,38].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Three cancer-related deaths were considered unrelated to the BNT162b2 vaccine 36 . One patient died due to myocardial infarction -the authors cannot complete rule out that this event was vaccine Questionnaire 39,41 . Review of medical records 42 .…”
Section: Institutional Review Boardsmentioning
confidence: 92%
“…2nd dose AEs: fever 5.8% -14.1%, local reactions 12.6% -33.46%, fatigue 10.4% -8.9%, arthralgia/myalgia 5.2% 38 . Overall: 45% -69% injection site pain, myalgia 9.5% -15%, bone No grade 3 / 4 side effects were recorded 18,35,37,39,41,42 . Low rate of grade 3 / 4 AE: 2.1% vaccine related AE grade 3 16 , 3.3% of patients after the 1st inoculum and 1.4% after the booster 38 .…”
Section: Institutional Review Boardsmentioning
confidence: 93%